Revision of the subgenus Stegana (Steganina) from China, with assessment of species delimitation using DNA barcodes (Diptera, Drosophilidae) - Wang, Ya-Lian; Li, Bing-Xue; Cui, Meng-Di; Zhang, Yuan; Wang, Le; Zhang, Cai-Hong; Tsaur, Shun-Chern; Chen, Hong-Wei; Huang, Jia (Zootaxa, 2023)
A total of 58 (eight known and 50 new) species of the subgenus Stegana (Steganina) from China were surveyed and (re)described: S. (S.) bacilla Chen & Aotsuka, 2004, S. (S.) belokobylskiji Sidorenko, 1997, S. (S.) hirticeps Wang, Gao, & Chen, 2013, S. (S.) izu Sidorenko, 1997, S. (S.) kanmiyai Okada & Sidorenko, 1992, S. (S.) masanoritodai Okada & Sidorenko, 1992, S. (S.) maymyo Sidorenko, 1997, stat. rev., S. (S.) nigripes Zhang & Chen, 2015, S. (S.) alafoliacea Zhang & Chen, sp. nov., S. (S.) baoxing Li & Chen, sp. nov., S. (S.) bibarbata Li & Chen, sp. nov., S. (S.) bimai Cui & Chen, sp. nov., S. (S.) cinereipecta Zhang & Chen, sp. nov., S. (S.) cardua Cui & Chen, sp. nov., S. (S.) cordhirsuta Wang & Chen, sp. nov., S. (S.) cornuta Li & Chen, sp. nov., S. (S.) cucullata Li & Chen, sp. nov., S. (S.) cultella Cui & Chen, sp. nov., S. (S.) curvitabulata Cui & Chen, sp. nov., S. (S.) daiya Cui & Chen, sp. nov., S. (S.) dendrophila Zhang & Chen, sp. nov., S. (S.) flabella Li & Chen, sp. nov., S. (S.) flavipes Li & Chen, sp. nov., S. (S.) formosa Zhang & Chen, sp. nov., S. (S.) fusca Li & Chen, sp. nov., S. (S.) fuscipes Li & Chen, sp. nov., S. (S.) glaucopalpula Cui & Chen, sp. nov., S. (S.) haba Zhang & Chen, sp. nov., S. (S.) hirticlavata Cui & Chen, sp. nov., S. (S.) iaspidea Zhang & Chen, sp. nov., S. (S.) idiasta Cui & Chen, sp. nov., S. (S.) kanda Cui & Chen, sp. nov., S. (S.) labao Li & Chen, sp. nov., S. (S.) lancang Li & Chen, sp. nov., S. (S.) latifoliacea Wang & Chen, sp. nov., S. (S.) liusanjieae Li & Chen, sp. nov., S. (S.) magniflava Cui & Chen, sp. nov., S. (S.) mailangang Li & Chen, sp. nov., S. (S.) marenubila Cui & Chen, sp. nov., S. (S.) menghai Zhang & Chen, sp. nov., S. (S.) menglian Li & Chen, sp. nov., S. (S.) minutiflava Li & Chen, sp. nov., S. (S.) multiprocera Li & Chen, sp. nov., S. (S.) nayun Li & Chen, sp. nov., S. (S.) nigridentata Wang & Chen, sp. nov., S. (S.) nigripalpula Cui & Chen, sp. nov., S. (S.) otphylla Cui & Chen, sp. nov., S. (S.) radiciflava Zhang & Chen, sp. nov., S. (S.) rava Cui & Chen, sp. nov., S. (S.) sciophila Li & Chen, sp. nov., S. (S.) septencolorata Li & Chen, sp. nov., S. (S.) serrata Zhang & Chen, sp. nov., S. (S.) silvestrella Zhang & Chen, sp. nov., S. (S.) simola Cui & Chen, sp. nov., S. (S.) yani Li & Chen, sp. nov., S. (S.) yixiang Zhang & Chen, sp. nov., S. (S.) zaduo Cui & Chen, sp. nov., and S. (S.) zhuoma Cui & Chen, sp. nov. We also provided a complete list of Chinese Steganina species together with their geographical distributions. In addition, the majority of currently available DNA barcode (partial sequence of the mitochondrial cytochrome c oxidase subunit I (COI) gene) sequences of this subgenus (435 sequences of 102 spp.) were employed in a molecular analysis for species delimitation. Taken together, morphology- and molecular-based species delimitation results reached a consensus for an overwhelming majority of these Steganina species (98 of 102 spp.).